Peryfraza: zakres oraz zawartość pojęcia - Sikorska, Marina (Acta Polono-Ruthenica, 2012)
The article studies the scope and the content of the concept of periphrasis on the basis of a modern Russian novel Sonechka written by Ludmila Ulickaya, in which the phenomenon is often used. The basic and the secondary criteria of periphrasis were revealed by general analysis of dictionary definitions and by comparing them with other stylistic devices of language and speech.